Social DNA : Rethinking Our Evolutionary Past. - Martin, M. Kay (Berghahn Books, Incorporated, 2018)
What set our ancestors off on a separate evolutionary trajectory was the ability to flex their reproductive and social strategies in response to changing environmental conditions. Exploring new cross-disciplinary research that links this capacity to critical changes in the organization of the primate brain, Social DNA presents a new synthesis of ideas on human social origins ' challenging models that trace our beginnings to traits shaped by ancient hunting economies, or to genetic platforms shared with contemporary apes.